Relative performance and R&D competition - Toshihiro Matsumura; Noriaki Matsushima; Susumu Cato (Osaka University, Institute of Social and Economic Research (ISER), 2009)
This paper formulates a duopoly model in which firms care about relative profits as well as their own profits. Our purpose is to investigate the relationship between the weight of relative performance and R&D expenditure. We find a non-monotone relationship between the weight of relative performance in their objectives and their R&D levels. Both highly reciprocal (altruism) and negative reciprocal attitudes yield high levels of R&D, while the intermediate situations yield low levels of R&D.
Keywords: L21; O31; L13; 330; relative profit; innovation; spite; altruism